Forum: Militarization 2.0: Communication and the Normalization of Political Violence in the Digital Age. Issue 3 (2nd July 2020) - Jackson, Susan T; Crilley, Rhys; Manor, Ilan; Baker, Catherine; Oshikoya, Modupe; Joachim, Jutta; Robinson, Nick; Schneiker, Andrea; Grove, Nicole Sunday; Enloe, Cynthia
Abstract: Scholars of international relations frequently explore how states normalize the use of military force through processes of militarization, yet few have analyzed how new information and communication technologies impact on these processes. The essays in this forum address this gap, and consider the political significance of new technologies, new actors, and new practices that shape "Militarization 2.0" and normalize political violence in the digital age. The authors in this forum rely, to varying degrees, on common militarized tropes and dichotomies (such as authenticity, belonging, and (de)humanizing framings) that are key to militarization, including those devices that rest on gender, race/ethnicity, and heteronormativity. Moving beyond a military-centered approach to militarization, the authors' questions cover ministries of foreign affairs; the embodied performances of celebrity leaders and insurgency groups; arms producers, the military video game industry, and private military and security companies; and violence entrepreneurs. The forum closes with reflections from Cynthia Enloe.